(untitled) (Asian Journal of Ethnobiology, 2023)
Abstract. Mawadha NR, Febryano IG, Tsani MK, Duryat. 2023. Utilization of medicinal plants by the Lintang Tribe Community in Talang Baru Village, Empat Lawang District, Indonesia. Asian J Ethnobiol 6: 20-25. The use of plants as medicine is still maintained for generations. This study aimed to determine the plant species, parts, and habitus used as medicine by the Lintang Trible, Empat Lawang District, South Sumatra, Indonesia. Data were collected using a qualitative approach through in-depth interviews involving observations and documentation studies. Data analysis was carried out descriptively to determine the use of plants in traditional medicine. The results showed that 57 species of plants belonging to 35 families were used as medicine. The most widely used plant family was Zingiberaceae because they can grow easily and are widely used as cooking spices by the people in Talang Baru Village. The plant parts used were root, stem, fruit, flower, leaf, shoot, rhizome, sap, bark, and fruit skin. The leaf was the most widely used part of the plant because it is easy to obtain, has many properties, and removing several leaves will not damage the plants. The plants used can be found in various habitus, namely herb, vine, fern, palm, shrub, tree, and succulent plants. Herbs were the most used plants for medicine. The government should support the conservation of these medicinal plants by creating special places to cultivate medicinal plants so that they remain sustainable.